THANATOLOGY, HISTORICAL AND CULTURAL ASPECTS: A BRIEF DISCUSSION (Fiep Bulletin - online, 2013)
The long rise of science led to the development of technologies in an impressive degree of complexity and sophistication, which meant that researchers know the intimate mechanisms of the human body and allow greater longevity. This way, the disease is now seen as an enemy to be eliminated. The last existential result is, of course, death, however, this is avoided as all other philosophical and existential issues. The lack of spirituality characteristic of our modern technological society is reflected in the fact that health professionals, like the society as a whole, denies death. Within the scope of mechanistic science, the death cannot be qualified, taking into account the multiple dimensions that involve the phenomenon of death and dying. This article aimed to present a reflection on the Thanatology and their interfaces, focusing on aspects relating to its history, cultural impact and technological advancement. These thoughts bring subsidies that allow recognize that the relationship between the beliefs, knowledge and practices that involve Thanatology are included, in various stages of discussion, involving the care in its essence. However, it is necessary that these links do not accomplish itself, but are built with the participation of the patient, family, health professionals and organized society.
Keywords: Thanatology; History article; Bioethics